Phase-space representations of the Bloch equation - O'Connell, R. F. (2012)
We discuss the phase-space representation of the Bloch equation and present analytic expressions for two generalized classes of distribution functions. Series solutions to order of ħ2 are given. We conclude that the Wigner quantum corrections are the simplest among the two general classes of distribution functions.